A factors affecting the employees’ satisfaction towards Perak State Economic Planning Unit (UPEN) at Economic Planning Unit (UPEN) Perak State Secretary’s Office Ipoh Perak / Faizatun Nadia Ahmad Shadzili - Ahmad Shadzili, Faizatun Nadia (2011)
This study aims to explore A Factors Affecting the Employees’ Satisfaction towards Perak State Economic Planning Unit (UPEN). The scope of the study is only limited to employees in UPEN. By using a structured questionnaire, the sampling method that used in data collection was cluster sampling method. The descriptive statistics has been use in order to gather the information. In this study, there are three independent constructs namely facilities/services at workplace, employees’ relationship and welfare/chance for the employees while the dependent construct namely employees’ satisfaction. The result supported that the employees’ relationship and welfare/chance for the employees has a significant and direct influence on employees’ satisfaction. This study also assessed the significant difference of demographic profile to employees’ satisfaction towards UPEN. Based on the results, researcher identified that the respondent gender had influence their satisfaction where there is a significant difference of demographic profile on respondent gender. From the result, it is well recommended that the department has to engage in confidence building within its employee ecosystem by being proactive in ensuring employee welfare